Family business: A fertile ground for research on time, teams and positive organizational study - Sharma, P.; De Massis, A.; Gagné, Marylène (2014)
Further reflecting on the study of organizational behaviour (OB) in family business (FB), this rejoinder piece discusses and integrates the points raised in the three thoughtful commentaries and our original article. We start by highlighting the general agreement between us and the commentators on three points: (1) that family firms are theoretically distinct from non-family firms due to significant involvement of kinship ties in the enterprise; (2) there is paucity of research at the interface of OB and FB and (3) there is an abundance of interesting research questions at this interface with the potential to benefit both domains of study. Next, we discuss and elaborate on the research possibilities on time, teams and positive organizational study, suggested by the commentators. An illustrative list of interesting research questions at the OB-FB interface that extend and enrich our agenda for future research is shared. We conclude that not only is FB a promising context for behavioural scholars to investigate, the timing is perfect for such investigations.